Using carbonaceous nanoparticles as surfactant carrier in enhanced oil recovery: A laboratory study. (15th June 2018) - Chen, Changlong; Wang, Shuoshi; Kadhum, Mohannad J.; Harwell, Jeffrey H.; Shiau, Bor-Jier
Graphical abstract: Highlights: Surfactant suspended nanoparticles exhibited very low adsorption in Ottawa sand. Nanoparticles delivered and spontaneously released surfactants to the O/W interface. Nanoparticles-amended surfactant system obtained ultralow IFT between oil and water. Nanoparticles-amended surfactant system achieved faster and higher tertiary oil recovery. Abstract: Carbonaceous nanoparticles multi-walled carbon nanotubes (MWNTs) and carbon blacks (CBs) exhibit promising properties for potential applications in crude oil production. The combination of large specific surface area and the strong affinity toward surfactants of nanoparticles mark their candidacy for delivering surfactant deep inside the reservoir. This study is aimed to assess the feasibility of surfactant carriers in tertiary oil recovery. Stable dispersions of aqueous-phase MWNTs or CBs that are formulated and able to propagate through the reservoir medium (3 wt% brine and 60 °C) were first examined as a prerequisite for reservoir application. Competitive adsorption of surfactant on nanoparticles was beneficial to decrease adsorptive loss on Ottawa sand at equilibrium concentration below critical micelle concentration (CMC). As a proof of concept, phase behavior of a ternary surfactant microemulsion system confirmed that the chosen nanoparticles (100 mg/L) successfully delivered surfactants and spontaneously released them to the O/W interface. The observed phenomenon is in accordance with calculation of the Gibbs free energy associated with oil/water/surfactant system. Besides, surfactants carried by nanoparticles achieved equilibrium ultralow interfacial tension between excess oil and aqueous phase similar to the value of surfactant-only formulation (0.007–0.009 mN/m). In one-dimensional sand pack tests, injection of MWNT-surfactant blend achieved faster and higher tertiary recovery than surfactant-only formulation, with cumulative tertiary oil recovery of 42.7% versus 38.1%. It has been noticed that once surfactant been released, destabilization of nanoparticle dispersion occurred and thus increased their retention in porous medium. In case of tight formations, further improvements may be addressed by applying functionalized carbonaceous nanoparticles to assure their transport in porous media after release of surfactant.